Nonexistence of positive solutions to nonlinear nonlocal elliptic systems - Dahmani, Zoubir; Karami, Fahd; Kerbal, Sebti (Journal of Mathematical Analysis and Applications, 2008)
In this paper we consider the question of nonexistence of nontrivial solutions for nonlinear elliptic systems involving fractional diffusion operators. Using a weak formulation approach and relying on a suitable choice of test functions, we derive sufficient conditions in terms of space dimension and systems parameters. Also, we present three main results associated to three different classes of systems.
Keywords: Fractional diffusion operator Nonlinear elliptic systems